Focus on biosafety in Nigeria - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
a workshop was held to develop the country's capability for the implementation of biosafety guidelines. The workshop was held at the International Institute of Tropical Agriculture (IITA), Ibadan, from 1620 January 1995.